Identification of material parameters based on a homogenization method using EBSD data - Tung, Phan Van (Vietnam Journal of Mechanics, 2015)
In this paper, an optimized homogenization method using uniaxial tensile tests to estimate material parameters in the micromechanical model of a heat treated DC04 steel is introduced. The method is based on a representative element model for the macroscopically homogeneous material. A Taylor polycrystal model is applied at integration points and simultaneously accounting for experimental electron backscatter diffraction (EBSD) data. Computational macro stress-strain curves are compared to experimental stress-strain curves to estimate the parameters of the DC04 steel at the different angles to rolling direction (RD).